Current and future use of vitamin D3 in patients with COVID-19 - I. N. Sychev; A. V. Matveev; D. A. Sychev (Качественная клиническая практика, 2020)
There is currently no evidence for vitamin D3 effectiveness for COVID-19 treatment and prevention.